Analisis Ekspektasi Kinerja dan Fitur Layanan Untuk Meningkatkan Minat Guna Mobile Banking - Anggraeni, Selvi; Ramdan, Asep Muhamad; Saori, Sopyan (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The development of technology and information that continues to grow rapidly in the era of globalization has a positive impact on society, one of which is conducting online financial transactions. This research was conducted with the aim of knowing how much influence performance expectations and service features have on interest in using BRImo m-banking in Sukabumi City. The research method used is quantitative with an associative descriptive research design. The population in this study are BRI Bank customers in Sukabumi City, using a simple random sampling method. This research was conducted by distributing online questionnaires to 397 respondents. The data analysis technique used is multiple linear regression with the help of data processing using IBM SPSS 24 Software. The results of this study indicate that performance expectations (X1) have a positive and significant effect on interest in using (Y), service features (X2) have a positive and significant effect interest in using (Y).